The Use of Telenursing through The Nursing Care - Maria Franciska Vianney Boro; Rr. Tutik Sri Hariyati (Poltekkes Kemenkes Semarang, 2019)
Background: Information technology that is increasingly developing, especially in the world of health today, makes people more sensitive to the professionalism of nursing care. But in Indonesia itself, against the background of the archipelago, the achievement of professional nursing care still seems to be an obstacle. This condition also resulted in the weak quality of health received, especially for regions that have not been exposed to technological developments. Telenursing is present as an answer to address the health problems of the nursing world as one of the nurses' efforts to help achieve equitable community welfare. Telenursing itself is one of the telecommunications technologies used to provide nursing care using information and data obtained remotely.Purpose: To illustrate the implementation of the use of telenursing through the provision of nursing care by professional nurses that is systematically integrated and focuses on the effectiveness of the results of the applicative telenursing itself.Methods: Literature review is to use PRISMA by examining several online databases that are adapted to the application of telenursing in nursing practice.Results: this shows that the presence of telenursing can help improve more comprehensive access and improve the quality of health services to achieve community welfare.Conclusion: Telenursing must be utilized appropriately and integrated so that the main objective of fulfilling public health, especially for those who are far from health services can be achieved.